A novel 3D biofabrication strategy to improve cell proliferation and differentiation of human Wharton’s jelly mesenchymal stromal cells for cell therapy and tissue engineering - Blanco-Elices, Cristina; Oruezabal, Roke Iñaki; Sánchez-Porras, David; Chato-Astrain, Jesús; Campos, Fernando; Alaminos, Miguel; Garzón, Ingrid; Campos, Antonio (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: Obtaining sufficient numbers of cells in a short time is a major goal of cell culturing in cell therapy and tissue engineering. However, current bidimensional (2D) culture methods are associated to several limitations, including low efficiency and the loss of key cell differentiation markers on cultured cells. Methods: In the present work, we have designed a novel biofabrication method based on a three-dimensional (3D) culture system (FIBRIAGAR-3D). Human Wharton’s jelly mesenchymal stromal cells (HWJSC) were cultured in 3D using 100%, 75%, 50% and 25% concentrations of fibrin-agarose biomaterials (FA100, FA75, FA50 and FA25 group) and compared with control cells cultured using classical 2D systems (CTR-2D). Results: Our results showed a significant increase in the number of cells generated after 7 days of culture, with cells displaying numerous expansions towards the biomaterial, and a significant overexpression of the cell proliferation marker KI67 was found for the FA75 and FA100 groups. TUNEL and qRT-PCR analyses demonstrated that the use of FIBRIAGAR-3D was not associated with an induction of apoptosis by cultured cells. Instead, the 3D system retained the expression of typical phenotypic markers of HWJSC, including CD73, CD90, CD105, NANOG and OCT4, and biosynthesis markers such as types-I and IV collagens, with significant increase of some of these markers, especially in the FA100 group. Finally, our analysis of 8 cell signaling molecules revealed a significant decrease of GM-CSF, IFN-g, IL2, IL4, IL6, IL8 and TNFα, suggesting that the 3D culture system did not induce the expression of pro-inflammatory molecules. Conclusion: These results confirm the usefulness of FIBRIAGAR-3D culture systems to increase cell proliferation without altering cell phenotype of immunogenicity and opens the door to the possibility of using this novel biofabrication method in cell therapy and tissue engineering of the human cornea, oral mucosa, skin, urethra, among other structures.